2017
DOI: 10.1177/1753193417728426
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of cold sensitivity in upper extremity nerve compression syndromes

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
2
10
2
Order By: Relevance
“…Our results confirm that cold sensitivity is more associated with several other symptoms, as demonstrated by higher symptom scorings for pain, numbness, stiffness and weakness, among cases who scored their cold sensitivity as moderate or severe than among cases who scored their cold sensitivity as mild. One smaller previous study (n = 100) reported cold sensitivity in 52% of patients with CTS or ulnar nerve compression at the elbow 4 . Another study, using the Boston Carpal Tunnel Questionnaire, of the evaluated outcome after OCTR in 102 hands reported cold sensitivity, defined as colour changes or severe pain in the fingers after exposure to cold, in 46/102 (45%) cases.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our results confirm that cold sensitivity is more associated with several other symptoms, as demonstrated by higher symptom scorings for pain, numbness, stiffness and weakness, among cases who scored their cold sensitivity as moderate or severe than among cases who scored their cold sensitivity as mild. One smaller previous study (n = 100) reported cold sensitivity in 52% of patients with CTS or ulnar nerve compression at the elbow 4 . Another study, using the Boston Carpal Tunnel Questionnaire, of the evaluated outcome after OCTR in 102 hands reported cold sensitivity, defined as colour changes or severe pain in the fingers after exposure to cold, in 46/102 (45%) cases.…”
Section: Discussionmentioning
confidence: 94%
“…In cases of nerve compression syndromes in the upper extremity, earlier studies have described cold sensitivity as occurring more commonly in patients with diabetes and in women 4 . Cold sensitivity largely resolves following open carpal tunnel release (OCTR), but may persist longer in patients with diabetes than in those without 5 .…”
Section: Introductionmentioning
confidence: 98%
“…Patients with median and ulnar nerve injuries who have no return of sensory function may have more severe cold intolerance (Irwin et al., 1997; Novak, 2018; Novak and Mackinnon, 2016; Ruijs et al., 2007; Wendt et al., 2018). Severe cold intolerance affects daily life, activity pattern, activity participation, roles, and quality of life (Carlsson et al., 2008; Novak and Mackinnon, 2016; Vaksvik et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of cold intolerance has been found higher in patients with nerve transections than in nerve compression neuropathies (Novak, 2018; Wendt et al., 2018). The aim of the present study is to investigate the relationship between cold intolerance and sensory function after nerve transection or compression neuropathy and to compare the severity of cold intolerance between patients with these two types of injury.…”
Section: Introductionmentioning
confidence: 99%
“…Cold intolerance, which is the mainstay of CISS questionnaire, is usually seen among the hand-injured patients. This debilitating symptom persists, causing a serious problem as it affects an individual’s daily life and performance at work [16, 19, 21, 26, 27]. The mechanism of cold sensitivity is still under debate, to identify whether it is caused by a thermoregulatory dysfunction or by a neurologic condition that triggers neuropathic pain, which is again applicable to that of HAVS.…”
Section: Discussionmentioning
confidence: 99%